Ketangguhan Dan Stres Akademik Pada Mahasiswa Tingkat Akhir: Sebuah Kajian Literatur - Suryani, Desak Ayu; Harumi, B. Primandini Yunanda (Jurnal Ilmiah Wahana Pendidikan, 2024)
Academic stress is a stressful condition experienced by individuals, the cause of which is academic demands that exceed the individual's resources and abilities. Furthermore, hardinnes is an individual's pattern or strategy in turning stressful events into challenges. The aim of this literature review is to identify factors that influence academic stress and to understand the picture of hardiness in final students who are working on their thesis. Searching for articles in this literature review was carried out using the electronic databases Google Scholar, SAGE Journal, Science Direct and Garuda Journal. The results of this research are that there are several factors that influence academic stress as well as a picture of the dynamics of final year students' hardiness in working on their thesis.